2022
DOI: 10.3390/ijerph191710488
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Resident Need-for-Physical-Assistance Scale in Eldercare: Validation Using 4716 Observation Sequences of Caring Activities

Abstract: Accurate and simple measures for classifying nursing home residents according to their care needs would be valuable for planning eldercare work. Our aim was to validate a developed classification scale of residents’ need for physical assistance. Eldercare workers and managers in 20 Danish nursing homes classified 1456 residents into four categories (from light to complete need for physical assistance). We validated the resident need-for-assistance scale against 4716 workplace observation sequences of caring ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Using the same dataset, Kyriakidis et al [ 35 ] found a positive association between the number of patients with a higher need for physical assistance and the number of patient handlings during a worker’s shift, indicating a higher physical workload of the entire shift with an increased number of patients with a high ADL score. The research conducted by Czuba et al [ 34 ], Jacobsen et al [ 22 ], and Kyriakidis et al [ 35 ] align well with the current study, and along with the current study, suggest that increased standing time during assignments, may coincide with an increased number of manual handlings of patients, thus presenting an increased risk of musculoskeletal pain [ 36 , 37 ]. Viewing the current study in the broader context of the aforementioned studies suggest that ADL self-care scores in Norwegian home care organization may be indicative not only of standing time but also of the frequency of manual patient handling, and cardiovascular strain on home care workers.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Using the same dataset, Kyriakidis et al [ 35 ] found a positive association between the number of patients with a higher need for physical assistance and the number of patient handlings during a worker’s shift, indicating a higher physical workload of the entire shift with an increased number of patients with a high ADL score. The research conducted by Czuba et al [ 34 ], Jacobsen et al [ 22 ], and Kyriakidis et al [ 35 ] align well with the current study, and along with the current study, suggest that increased standing time during assignments, may coincide with an increased number of manual handlings of patients, thus presenting an increased risk of musculoskeletal pain [ 36 , 37 ]. Viewing the current study in the broader context of the aforementioned studies suggest that ADL self-care scores in Norwegian home care organization may be indicative not only of standing time but also of the frequency of manual patient handling, and cardiovascular strain on home care workers.…”
Section: Discussionsupporting
confidence: 86%
“…They also found a strong trend for an increased proportion of direct patient care tasks with patients of higher ADL scores. In Denmark, nursing homes have no standardized rating of patients’ care needs, so Jacobsen et al [ 22 ] created and validated a patient rating scale as a proxy for the physical work demands of the workers. They used observational data from 1456 patients to assess the physical work demands for four patient categories: in need of “light”-, “moderate”-, “extensive”- to “complete”- physical assistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They communicated that the patient visits were unevenly distributed among the home care workers, in terms of patients requiring extensive care and light care. We examined the patients’ ADL scores, assuming that they reflect the level of care for the patient, and thus can serve as a proxy for the physical work demands of the home care worker [ 20 , 21 ]. To check this assumption, we used objective physical activity data from a feasibility study in home care and associated them with ADL scores of the patients visited during selected shifts.…”
Section: Methods—participants Interventions and Outcomesmentioning
confidence: 99%
“…In addition, the strenuous tasks were unevenly distributed among workers and a substantial proportion of employees were exposed to very high levels of physical strain [ 2 ], likely to lead to a substantial risk of musculoskeletal pain and sickness absence. Available evidence indicates that strenuous activities such as pulling, pushing, lifting, and leaning forward are frequently performed by home care workers caring for patients with extensive care needs [ 20 , 21 ]. Patients who are admitted into the Norwegian home care system, are assessed by a trained nurse in terms of their care needs based on the International Classification of Functioning, Disability and Health system developed by WHO [ 22 , 23 ], resulting in an activities of daily living (ADL) score.…”
Section: Introductionmentioning
confidence: 99%